The Theory of Cost and Production in the Multi-Product Firm - Pfouts, Ralph W. (Econometrica, 1961)
THE MULTI-PRODUCT firm occupies a prominent place among important but neglected topics in economic theory. Barring the programming approaches, a search of the literature reveals no comprehensive theoretical treatment of the subject. Indeed the brief development by Hicks in the mathematical appendix to Value and Capital [6] is probably the most thorough treatment in the sense of considering both the production and sales activities of the firm. Since Hicks allots only four pages to this topic, this is a remarkable state of affairs. While the literature on all phases of the multi-product firm is scanty, a few writers have considered the selling side of such a firm; the works of Bailey [1], Clemens [3], and Weldon [10] may be cited in this connection. On the cost and production side the literature is virtually non-existent. Even the work of Carlson [2], a standard reference for twenty years, deals only with the special case of joint cost but not with any other aspect of the multi-product firm. The purpose of this paper is to present a theory of cost and production for the multi-product firm. In developing this theory, the traditional concept of the firm as a social mechanism that connects the markets for factors of production with the markets for finished products will be retained. This is in contrast to the usual inward looking view of the firm that appears in the programming literature. But once the problem is clearly stated in traditional terms, it becomes apparent that the Kuhn-Tucker theorem, which can be thought of as the logical basis of the optimization techniques of activity analysis, can be used in a straightforward way to solve the problems of cost and production in the multi-product firm. The solution of the problem will show that the optimum conditions for the multi-product firm are different from those of the single-product firm. These differences are discussed briefly in the final section of the paper.